2019
DOI: 10.1088/1757-899x/660/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Environmental study and valorization of an ashy waste: case of pyrrhotite ash

Abstract: Pyrrhotite ash is an industrial waste which is currently stored in large quantities in a large area in southwest of Morocco. The literature review revealed that this waste has been used by some cement industries and has not been the subject of any environmental study or valuation in another area. This work focuses on the environmental study of pyrrhotite ash. This study consists of a dynamic test with renewing lixiviate more particularly the leaching tank test. The protocol used is extracted from the Dutch sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Pyrrhotite ash was chosen to this end. It is a mineral waste that was studied and valorized for the first time in our previous work [19,21]. The physicochemical characterization of the pyrrhotite ash showed that it is a mineral waste rich in hematite, silica and alumina.…”
Section: Brick Heat Treatment Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyrrhotite ash was chosen to this end. It is a mineral waste that was studied and valorized for the first time in our previous work [19,21]. The physicochemical characterization of the pyrrhotite ash showed that it is a mineral waste rich in hematite, silica and alumina.…”
Section: Brick Heat Treatment Programmentioning
confidence: 99%
“…So the material fills the volume more compactly [19]. Another work dedicated to the study of the behavior of pyrrhotite ash towards the environment has been published [21].…”
Section: Brick Heat Treatment Programmentioning
confidence: 99%
See 1 more Smart Citation